2002
DOI: 10.1016/s0006-291x(02)00907-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of disulfide bond formation in the folding and assembly of the envelope glycoproteins of a pestivirus

Abstract: Bovine viral diarrhea virus (BVDV) is a pestivirus member of the Flaviviridae family, closely related to, and used as a surrogate model for the hepatitis C virus. Its envelope contains the E1 and E2 glycoproteins, disulfide linked into homo- and heterodimers. In this study, we investigate the role of disulfide bond formation in the folding, assembly, and stability of BVDV glycoproteins. We provide molecular evidence that intact disulfide bonds are critical for the acquirement of a stable conformation of E2 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
(37 reference statements)
2
8
1
Order By: Relevance
“…This is in concert with our former findings that MAb BVD/C42 does not react with the Erns protein in Western blot under reducing conditions. In contrast, it could be demonstrated previously that E2 dimers are resistant to reducing agents and degradation and possess a pH stability (Branza-Nichita et al, 2002) which supports our findings. Biochemically, BVDV infection of susceptible cells was inhibited by two drugs that interfere with the clathrindependent pathway but not by drugs that inhibit the caveolae-dependent pathway.…”
Section: Discussionsupporting
confidence: 93%
“…This is in concert with our former findings that MAb BVD/C42 does not react with the Erns protein in Western blot under reducing conditions. In contrast, it could be demonstrated previously that E2 dimers are resistant to reducing agents and degradation and possess a pH stability (Branza-Nichita et al, 2002) which supports our findings. Biochemically, BVDV infection of susceptible cells was inhibited by two drugs that interfere with the clathrindependent pathway but not by drugs that inhibit the caveolae-dependent pathway.…”
Section: Discussionsupporting
confidence: 93%
“…It is not clear why potentially misfolded HCV glycoproteins accumulate in the ER of infected insect cells. This result differs from those obtained with BVDV, where it was shown that misfolded glycoproteins were degraded by the proteasome and did not accumulate in the ER of BVDV-infected Madin-Darby bovine kidney cells (Branza-Nichita et al, 2002). This accelerated degradation of misfolded BVDV glycoproteins caused a reduction in the amount of prebudding complexes, which was proposed tentatively as one possible explanation for the inhibition of viral secretion.…”
Section: Discussioncontrasting
confidence: 87%
“…Moreover, a disulfide bridge is established with E2 leading to covalently bound heterodimers. The formation of the E1-E2 heterodimer is slow (R€ umenapf et al, 1993) which might be due to the slow folding of E1 (Branza-Nichita, Durantel, Carrouee-Durantel, Dwek, & Zitzmann, 2001;Branza-Nichita, Lazar, Durantel, Dwek, & Zitzmann, 2002). E1 interacts transiently with calnexin (>30 min), and the formation of E1-E2 heterodimers starts after correct folding and release of E1 from calnexin.…”
Section: E1mentioning
confidence: 99%